(untitled) (Research, Society and Development, 2022)
Purpose: The purpose of this laboratory study was to differentiate the color of natural dentin (ND) and dentin porcelain (DP) by using three brands of Glass-Matrix Ceramic System (GMCS) by parametric CIE L*, a*, b* system. Materials and methods: An extracted human upper central incisor was prepared as a control group. Uniformly thick dentin specimen was taken from the middle coronal third of the labial half longitudinally. Twelve disks of GMCS dentin porcelain were fabricated according to manufactures’ instructions by using conventional powder/slurry technique, 4 disks for each group; Feldspathic ceramic VITA VMK 95 (VMK), Leucite-based ceramic VITA VM9 (VM9), and Fluorapatite-based ceramic IPS e.max Ceram IVOCLAR (IEC). ND and DP specimens’ thickness were (8×1 mm, shade A3) and (n=4). A digital camera was used to take samples’ photos while the color readings were obtained by graphic software. The specimens’ colors were measured, and the data were statistically evaluated using Levene’s test, One-way ANOVA, and Post Hoc Multiple Comparisons. Results: Parametric CIE L*, a*, b*, and ΔE values of all ceramic disks compared to ND were significantly different even within ceramic brands (P<.05), ΔE were ND > IEC > VMK > VM9. Conclusions: To reproduce ND color by DP needs proper color shade guide selection due to color differences from one brand to another even in the same shade guide tab. Clinical Significance: There is a lack of information on how identical natural dentin color to dentin porcelain is at the same shade guide.